2019
DOI: 10.3389/fpls.2019.00246
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Epigenetic Regulation in the Adaptation and Stress Responses of Non-model Plants

Abstract: In recent years enormous progress has been made in understanding the role of epigenetic regulation response to environmental stimuli, especially in response to stresses. Molecular mechanisms involved in chromatin dynamics and silencing have been explained, leading to an appreciation of how new phenotypes can be generated quickly in response to environmental modifications. In some cases, it has also been shown that epigenetic modifications can be stably transmitted to the next generations. Despite this, the vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 55 publications
1
130
1
3
Order By: Relevance
“…Transgenerational effects of the parental environment on offspring phenotype might also be caused by stress-induced epigenetic modifications of the offspring genome (Jablonka and Raz, 2009;Hauser et al, 2011;Herman and Sultan, 2011;Holeski et al, 2012). Epigenetic modifications, primarily DNA methylation and histone modifications, alter the patterns and magnitude of gene expression and are known to influence plant growth and reproduction (Pikaard and Scheid, 2014;Campos-Rivero et al, 2017), plant response to stress (Chinnusamy and Zhu, 2009;Thiebaut et al, 2019), and the transgenerational induction of plant defenses (Holeski et al, 2012). It is possible that epigenetic modifications of the plant genome contribute to the independent transgenerational impact of herbivory that we observed.…”
Section: Maternal Effects and Epigenetic Modifications May Contributementioning
confidence: 99%
See 1 more Smart Citation
“…Transgenerational effects of the parental environment on offspring phenotype might also be caused by stress-induced epigenetic modifications of the offspring genome (Jablonka and Raz, 2009;Hauser et al, 2011;Herman and Sultan, 2011;Holeski et al, 2012). Epigenetic modifications, primarily DNA methylation and histone modifications, alter the patterns and magnitude of gene expression and are known to influence plant growth and reproduction (Pikaard and Scheid, 2014;Campos-Rivero et al, 2017), plant response to stress (Chinnusamy and Zhu, 2009;Thiebaut et al, 2019), and the transgenerational induction of plant defenses (Holeski et al, 2012). It is possible that epigenetic modifications of the plant genome contribute to the independent transgenerational impact of herbivory that we observed.…”
Section: Maternal Effects and Epigenetic Modifications May Contributementioning
confidence: 99%
“…Epigenetic modifications can alter gene expression through DNA methylation, histone modifications, and small-RNA biosynthesis, and are known to regulate plant growth, development, and reproduction (Pikaard and Scheid, 2014;Campos-Rivero et al, 2017). Previous studies have shown that both biotic and abiotic stresses can induce heritable epigenetic modifications in plants that can affect offspring phenotypes (see reviews by Holeski et al, 2012;Thiebaut et al, 2019). Furthermore, there is evidence that epigenetic modifications play a role in inbreeding depression (Vergeer et al, 2012).…”
mentioning
confidence: 99%
“…Patterns of DNA methylation can also vary independently from genetic variation (Klironomos et al, 2013;Cortijo et al, 2014;Kooke et al, 2015;van der Graaf et al, 2015;Wilschut et al, 2016) and can change in response to environmental variation. For example, genome-wide remodeling of DNA methylation has been documented in response to both biotic factors (infectious pathogens, herbivory, and plant-plant competition) and abiotic factors (light, temperature, nutrient availability, and precipitation) (Verhoeven et al, 2010a;Dowen et al, 2012;Dubin et al, 2015;Secco et al, 2015;Kawakatsu et al, 2016;Alonso et al, 2019;Thiebaut et al, 2019). Furthermore, the methylomes of some plants show signatures of local adaptation and geographic provenance (Platt et al, 2015;Kawakatsu et al, 2016;Wilschut et al, 2016;Busconi et al, 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which such defense phenotypes may be transmitted across seasons through rhizamatous offshoots (or via seeds) are not well understood, but it is likely that epigenetics plays a role via DNA methylation patterns that control gene expression patterns (Latzel and Klimešová 2010;Verhoeven and Preite 2014;Latzel et al 2016;Thiebaut et al 2019). Numerous studies across a variety of plant-herbivore systems have shown that herbivory by chewing insects results in the induction of a battery of direct and indirect defenses in plants, which are typically mediated by the phytohormone jasmonic acid (JA) (Howe 2004;Boughton et al 2005;Howe and Jander 2008).…”
Section: Discussionmentioning
confidence: 99%